Mapping of Blood Coagulation via Image Processing Method - Onar, B.; Bayindir, M. I.; Bilgili, H.; Erkurt, M. A.; Yakinci, C.; Yakinci, M. E. (Ieee, 2015)
Biomedical applications based on image process algorithms are developed to aid doctors for diagnostic of some diseases. Several conventional tests are available about measuring blood coagulation such as PTZ, aPTZ, PTZ-INR. These tests are performed before every surgical operation even during some critical operations especially in cardiovascular and liver operations. Then, images are taken by a microscope connected to a computer in every 15 seconds, in such a way that 45 images are obtained till end of coagulation. These images are processed in an image processing algorithm in Matlab software. Hence, a graphical representation is produced for every subject. Results obtained from the proposed method prove that it can be a useful alternative to conventional methods.
Medical Technologies National Conference (TIPTEKNO) -- OCT 15-18, 2015 -- Bodrum, TURKEY
Keywords: Coagulation; PTZ; INR